Validity and Reliability of Greek Versions of Two Scales Assessing Family and Friend Support for Exercise Behaviour. Issue 1 (February 2014) - Theodoropoulou, Eleni; Karteroliotis, Konstantinos; Stavrou, Nektarios
This study examined the validity and reliability of Greek versions of two scales assessing family and friend support for exercise behaviour. Exploratory factor analyses (EFAs) and confirmatory factor analyses (CFAs) were performed in a sample of 360 students. Additionally, CFAs were applied in a second sample of 726 physically active adults. Finally, associations were examined among scales and physical activity, exercise self-efficacy, and socio-demographic variables. Results indicated (a) a two-factor model for the Family Support for Exercise Behaviour Scale, (b) a one-factor solution for the Friend Support for Exercise Behaviour Scale, (c) satisfactory reliability coefficients, and (d) associations among the scales and physical activity, self-efficacy and socio-demographic variables. Conclusively, the social support scales were valid and reliable.